Post‐discharge patient‐reported non‐adherence to aspirin compared to enoxaparin for venous thromboembolism prophylaxis after hip or knee arthroplasty. Issue 4 (20th January 2023) - Sidhu, Verinder; Naylor, Justine M.; Adie, Sam; Bastiras, Durga; Buchbinder, Rachelle; Ackerman, Ilana; Harris, Ian A.
Abstract: Background: Aspirin and enoxaparin are commonly used for venous thromboembolism (VTE) prophylaxis following total hip arthroplasty (THA) or total knee arthroplasty (TKA). The purpose of this study was to compare non‐adherence after discharge to aspirin or enoxaparin following THA or TKA. Methods: A subset of participants in the CRISTAL study were selected for participation. Additional inclusion criteria were no preoperative anticoagulant use and discharge from hospital before the prophylaxis period ended. The first four consecutive patients from each arm at each participating hospital were planned to be recruited (planned sample size n = 248). A patient‐reported adherence questionnaire was completed by telephone at 36–41 days after THA and at 15–20 days after TKA. The primary outcome was non‐adherence. Secondary outcomes were number of missed doses and the reasons for non‐adherence. Results: There were 178 participants included from 15 sites, less than planned explained by early stopping of trial recruitment. There was no significant between‐group difference in patient‐reported non‐adherence: 24% (17/71) for aspirin, 30% (32/107) for enoxaparin, odds ratio = 1.4 (95% CI 0.7–2.9). The mean number of missed doses was 2.5 for aspirin and 3.4 for enoxaparin (mean difference = 0.9 doses, 95% CI −1.2 to 3.1). For aspirin, the most commonly reported reason for non‐adherence was forgotten doses and for enoxaparin it was clinician‐recommended change. Conclusions: Rates of non‐adherence and the number of missing doses were similar for patients regardless of drug prescribed. The most common reasons for non‐adherence were unrelated to the mode of administration. Abstract :